2009
DOI: 10.1210/en.2008-1251
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of G Protein-Coupled Receptor 39 Impairs Insulin Secretion in Vivo

Abstract: GPR39 is a G protein-coupled receptor expressed in liver, gastrointestinal tract, adipose tissue, and pancreas. We have recently shown that young GPR39(-/-) mice have normal body weight, food intake, and fasting glucose and insulin levels. In this study, we examined the role of GPR39 in aging and diet-induced obese mice. Body weight and food intake were similar in wild-type and GPR39(-/-) mice as they aged from 12 to 52 wk or when fed a low-fat/high-sucrose or high-fat/high-sucrose diet. Fifty-two-week-old GPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 39 publications
6
62
0
Order By: Relevance
“…Zinc secreted from β cells is known to affect neighboring endocrine cells (7,11). Consistent with previous reports (10,(14)(15)(16), addition of zinc to the perfusate (30 μM) markedly suppressed insulin hypersecretion in ZnT8KO mice, almost to control levels ( Figure 2D). Furthermore, the addition of zinc chelator calcium EDTA (2.5 mM) (7) significantly increased insulin secretion from isolated C57BL/6J islets ( Figure 5C and Supplemental Figure 2B).…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…Zinc secreted from β cells is known to affect neighboring endocrine cells (7,11). Consistent with previous reports (10,(14)(15)(16), addition of zinc to the perfusate (30 μM) markedly suppressed insulin hypersecretion in ZnT8KO mice, almost to control levels ( Figure 2D). Furthermore, the addition of zinc chelator calcium EDTA (2.5 mM) (7) significantly increased insulin secretion from isolated C57BL/6J islets ( Figure 5C and Supplemental Figure 2B).…”
Section: Introductionsupporting
confidence: 91%
“…However, in that study, the discrepancy between these 2 observations was not fully explored. Previous studies reported that insulin secretion from pancreatic islets was suppressed by zinc through enhanced outward current of the K-ATP channel (8)(9)(10)(14)(15)(16). Therefore, we rigorously examined whether zinc could suppress insulin secretion in various experimental settings, using isolated islets from ZnT8KO mice ( Figure 2B and Figure 5D), the addition of zinc chelator to C57BL/6J islets ( Figure 5C), and pancreas perfusion ( Figure 2D), in addition to simple comparison between control and ZnT8KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations